Penggunaan Media Visual Nilai-Nilai Pancasila dalam Pembelajaran PPKn - qiromah, Muflihatul (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
This research is motivated by the lack of public understanding of the values of Pancasila.thisstudy uses visual media toimprove learning achievement of Pancasila values andattitudesthat contain Pancasilavalues andmake learning more fun.Type of research used is fieldresearch.Data collection by observation and interview.Data were analyzed using qualitativeanalysis.Visual media research results in the from of Pancasila values in the from ofPancasilasymbols and pictures of Pancasilavalues using demonstration methods matchthevalue of Pancasila with Pancasila symbols in group showing visualization media Pancasilavalue are more effectiveto make learning more fun and visual media Pancasila values aremore effectivein increasing student motivation in learning that contains Pancasila values.